A Checking Method for Multiple Seismic Performance Objectives of Bridge Piers Designed According to Code Provisions. Issue 7 (2nd October 2016) - Sheikh, M. Neaz; Légeron, Frédéric
Abstract : Seismic bridge design codes require that bridge piers designed according to prescribed design rules should attain specified multiple seismic performance objectives. However, design codes do not explicitly require checking the attainment of specified performance objectives for designed bridge piers. In this article, seismic performance levels have been correlated with engineering damage parameters. A checking method for multiple seismic performance objectives of bridge piers has been outlined and validated with experimental results. The application of the method has been demonstrated by checking the performance of a bridge pier designed according to a code provision for a wide range earthquake ground motions.